Communication and Low Mood (CALM): a randomized controlled trial of behavioural therapy for stroke patients with aphasia - Thomas, Shirley A.; Walker, Marion F.; Macniven, Jamie A.; Haworth, Helen; Lincoln, Nadina (SAGE, 2013)
Objective: The aim was to evaluate behavioural therapy as a treatment for low mood in people with aphasia.